Volume 5: 35th Design Automation Conference, Parts a and B 2009
DOI: 10.1115/detc2009-86899
|View full text |Cite
|
Sign up to set email alerts
|

Modular Product Design Using Cyberinfrastructure for Global Manufacturing

Abstract: Modularization of parts — a fairly recent trend in product development — facilitates part definitions in a standardized, machine-readable form, so that we can define a part based on its input(s), output(s), features, and geometric information. Standardizing part definitions will enable manufacturing companies to more easily identify part suppliers in global, virtual environments. This standard representation of parts also facilitates modular product design during parametric design. We will show that this probl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(11 citation statements)
references
References 0 publications
0
11
0
Order By: Relevance
“…Contemporary decomposition methods use product modularization, and related interface specifications and requirements data, along with new "cyberinfrastructures" to evolve a product design among a globally distributed development team, see Yoo [33]. Multiuser CAx methods offer new advantages by simultaneously integrating a virtual team, thereby reducing the need for modularization by localization and specification assignment.…”
Section: Discussionmentioning
confidence: 99%
“…Contemporary decomposition methods use product modularization, and related interface specifications and requirements data, along with new "cyberinfrastructures" to evolve a product design among a globally distributed development team, see Yoo [33]. Multiuser CAx methods offer new advantages by simultaneously integrating a virtual team, thereby reducing the need for modularization by localization and specification assignment.…”
Section: Discussionmentioning
confidence: 99%
“…Hamacher [11] has shown that the k-best solutions of a linear integer network flow problem can be solved in polynomial time. Extending our earlier framework for the optimal design solution [3], in this paper, we present a cutting plane-based approach to find k-best design solutions, which extends our earlier work for finding the optimal design solution [3].…”
Section: Introductionmentioning
confidence: 96%
“…Modularization is a critical component of global collaboration in product development [1]. Recently, Bohm et al [2] have built a global design repository to store module information, while Yoo et al [3] have proposed a cyberinfrastructure for modular product design to publish/subscribe module information interactively, as shown in Fig. 1.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations